PELATIHAN BUDIKDAMBER TERINTEGRASI DAN BERKELANJUTAN USAHA MELALUI DIGITAL MARKETING DAN MANAJEMEN KEUANGAN KEPADA GURU DI SDN PANNYANGKALANG - Wahda; Insany Fitri Nurqamar; Asty Almaida; Farhana Ramdhani Sumardi; Ulumuddin, Ihya'; Muhammad Rifai; Muhammad Iqramul Hasyim; Yohanis Rantelino; Rifal; Akbar; et al. (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
In the era of globalization, teachers at SDN Pannyangkalang, Gowa Regency, South Sulawesi, face significant financial challenges, particularly as they rely solely on their salaries as the primary source of family income. This community service project aims to provide concrete solutions through the innovation of Budikdamber, an approach that combines fish farming in a bucket with a kangkung (water spinach) hydroponic system. This innovation not only offers a sustainable agricultural solution but also creates opportunities for economic improvement for the teachers. The program focuses on enhancing teachers' knowledge and skills in two crucial areas: digital marketing and financial management. A total of 15 teachers from SDN Pannyangkalang actively participated in this initiative, demonstrating enthusiasm and commitment to learning and applying new skills. Support from the school has strengthened the program’s potential to become a sustainable solution for improving both economic welfare and educational quality. Program evaluations indicate that Budikdamber has successfully emerged as an environmentally friendly agricultural model and an innovative solution to the economic challenges faced by teachers. The success of this program not only has a direct positive impact but also fosters sustainable change by integrating technological innovation, digital marketing, and improved financial management. It is expected to empower teachers to achieve greater economic independence, contributing to financial stability and the advancement of educational capacity at SDN Pannyangkalang. Therefore, this program can serve as a model for other schools facing similar challenges, promoting the overall well-being of the educational community. — Dalam era globalisasi, guru-guru di SDN Pannyangkalang, Kabupaten Gowa, Sulawesi Selatan, menghadapi tantangan finansial yang signifikan, terutama karena mereka hanya mengandalkan gaji sebagai sumber ekonomi keluarga. Pengabdian ini bertujuan memberikan solusi konkret melalui inovasi Budikdamber, yang merupakan singkatan dari budidaya ikan dalam ember, dikombinasikan dengan sistem hidroponik kangkung. Inovasi ini tidak hanya menawarkan solusi pertanian berkelanjutan tetapi juga membuka peluang peningkatan ekonomi bagi para guru. Program ini berfokus pada peningkatan pengetahuan dan keterampilan guru dalam dua aspek penting: digital marketing dan manajemen keuangan. Sebanyak 15 guru dari SDN Pannyangkalang berpartisipasi aktif dalam kegiatan ini, menunjukkan antusiasme dan komitmen terhadap pembelajaran dan penerapan keterampilan baru. Dukungan dari pihak sekolah membuat program ini berpotensi menjadi solusi berkelanjutan yang mampu meningkatkan kesejahteraan ekonomi dan kualitas pendidikan. Evaluasi program menunjukkan bahwa Budikdamber berhasil menjadi model pertanian ramah lingkungan dan solusi inovatif untuk tantangan ekonomi yang dihadapi para guru. Keberhasilan program ini tidak hanya memberikan dampak positif langsung tetapi juga mendorong perubahan berkelanjutan, dengan memadukan inovasi teknologi, pemasaran digital, dan peningkatan manajemen keuangan. Hal ini diharapkan dapat memberdayakan guru untuk mencapai kemandirian ekonomi yang lebih besar, berkontribusi pada stabilitas finansial, dan pengembangan kapasitas pendidikan di SDN Pannyangkalang. Dengan demikian, program ini dapat menjadi model bagi sekolah lain yang menghadapi tantangan serupa, mendorong peningkatan kesejahteraan komunitas pendidikan secara keseluruhan.